Pengaruh On the Job Training dan Kemampuan Kerja Karyawan di PT. PLN Persero Distribusi Jawa Barat - Diwangkara, Sultan; ., Sumiyati; Razati, Girang (Journal of Business Management Education (JBME), 2020)
Companies without good human resources in strategy and operations will not be able to achieve company goals. Success or failure of company goals can’t be separated from how the performance of its employees. Organizations are required to maintain their employees so as to produce good performance and employees can dedicate themselves to the organization where employees work. The problem of employee performance is still a serious problem for many companies both in manufacturing and services. One company that is experiencing performance problems is by PT. PLN Persero Distribution West Java. The efforts to be made by PT. PLN Persero Distribution West Java to improve performance that is by increasing on the job training and work ability to its employees. This study aims to obtain (1) implementation of on the job training, (2) description of work ability, (3) description of employee performance, (4) Effect of on the job training and work ability both partially and simultaneously. The object of the unit of analysis in this study is the employees of PT. PLN Persero Distribution West Java. The type of research used is descriptive and verification. The method used was an explanatory survey with a sample of 58 employees. The data analysis technique used is path analysis with Statistical Product for Service Solutions (SPSS) 24.0 computer software tools for windows. The findings in this study indicate that the picture on the job training is in the good category, a description of work ability in the good category. Variables that have an influence on employee performance are on the job training and work ability. Based on the results of this study, it is recommended that on the job training in companies be further improved in the aspect of job instruction training. In terms of work capabilities in the company improve intellectual abilities. So it is expected that on the job training and work skills need to be considered further by the company in supporting employee performance improvement.